Advection Drives Nitrate Past the Microphytobenthos in Intertidal Sands, Fueling Deeper Denitrification - Schutte, Charles A.; Huanca-Valenzuela, Paulina; Lavik, Gaute; Marchant, Hannah K.; de Beer, Dirk (Frontiers in Microbiology, 2021)
Nitrification rates are low in permeable intertidal sand flats such that the water column is the primary source of nitrate to the sediment. During tidal inundation, nitrate is supplied to the pore space by advection rather than diffusion, relieving the microorganisms that reside in the sand from nitrate limitation and supporting higher denitrification rates than those observed under diffusive transport. Sand flats are also home to an abundant community of benthic photosynthetic microorganisms, the microphytobenthos (MPB). Diatoms are an important component of the MPB that can take up and store high concentrations of nitrate within their cells, giving them the potential to alter nitrate availability in the surrounding porewater. We tested whether nitrate uptake by the MPB near the sediment surface decreases its availability to denitrifiers along deeper porewater flow paths. In laboratory experiments, we used NOx (nitrate + nitrite) microbiosensors to confirm that, in the spring, net NOx consumption in the zone of MPB photosynthetic activity was stimulated by light. The maximum potential denitrification rate, measured at high spatial resolution using microsensors with acetylene and nitrate added, occurred below 1.4 cm, much deeper than light-induced NOx uptake (0.13 cm). Therefore, the shallower MPB had the potential to decrease NOx supply to the deeper sediments and limit denitrification. However, when applying a realistic downward advective flow to sediment from our study site, NOx always reached the depths of maximum denitrification potential, regardless of light availability or season. We conclude that during tidal inundation porewater advection overwhelms any influence of shallow NOx uptake by the MPB and drives water column NOx to the depths of maximum denitrification potential.